Social media marketing in Vietnam: A study of consumer profiles - Trần, Thị Thu Trang (Đại học Quốc gia Hà Nội, 2016)
Constructing a questionnaire that can help company to create social media consumer profiles in Vietnam. Determining whether social media can be considered as an effective marketing channel, from the user perspectives. Deriving a list of commendations for marketing management for entering social media